Comfort and clinical events at the end of life of nursing home residents with and without dementia: The six‐country epidemiological PACE study. (10th March 2020) - Miranda, Rose; van der Steen, Jenny T.; Smets, Tinne; Van den Noortgate, Nele; Deliens, Luc; Payne, Sheila; Kylänen, Marika; Szczerbińska, Katarzyna; Gambassi, Giovanni; Van den Block, Lieve; ,
Abstract: Objectives: We aimed to investigate the occurrence rates of clinical events and their associations with comfort in dying nursing home residents with and without dementia. Methods: Epidemiological after‐death survey was performed in nationwide representative samples of 322 nursing homes in Belgium, Finland, Italy, the Netherlands, Poland, and England. Nursing staff reported clinical events and assessed comfort. The nursing staff or physician assessed the presence of dementia; severity was determined using two highly discriminatory staff‐reported instruments. Results: The sample comprised 401 residents with advanced dementia, 377 with other stages of dementia, and 419 without dementia (N = 1197). Across the three groups, pneumonia occurred in 24 to 27% of residents. Febrile episodes (unrelated to pneumonia) occurred in 39% of residents with advanced dementia, 34% in residents with other stages of dementia and 28% in residents without dementia ( P = .03). Intake problems occurred in 74% of residents with advanced dementia, 55% in residents with other stages of dementia, and 48% in residents without dementia ( P < .001). Overall, these three clinical events were inversely associated with comfort. Less comfort was observed in all resident groups who had pneumonia (advanced dementia, P = .04; other stages of dementia, P = .04; without dementia, P < .001). Among residents with intake problems, less comfort was observed only in those with other stages of dementia ( P < .001) and without dementia ( P = .003), while the presence and severity of dementia moderated this association ( P = .03). Developing "other clinical events" was not associated with comfort. Conclusions: Discomfort was observed in dying residents who developed major clinical events, especially pneumonia, which was not specific to advanced dementia. It is crucial to identify and address the clinical events potentially associated with discomfort in dying residents with and without dementia.